The effect of irradiation with accelerated electrons on the extraction of Pu with 30% solution of TBP in Isopar-M. (January 2017) - Belova, E.V.; Dzhivanova, Z.V.; Tkhorzhnitsky, G.P.; Stefanovsky, S.V.
Abstract: The variations of extraction characteristics towards plutonium of "30% TBP – Isopar-M – HNO3 " system under irradiation with accelerated electrons in cyclic mode of extractant use were investigated. It was found that the residual concentration of plutonium in the extractant after stripping over 15 cycles (520 kGy dose) increases twice, and during the regeneration step increases by 4–6 times. At the same time, the Pu distribution coefficient varies only slightly in cyclic mode. The formation of products with high molecular mass during hydrolysis leads to an increase in viscosity of the organic phase and hindering of the phase separation. Highlights: Effect of accelerated electrons on the extraction of Pu from nitric acid with 30% solution of TBP in Isopar-M was studied. Pu distribution coefficient is dependent on irradiation dose and decreases due to radiolytic decomposition of HNO3 . Increased density and viscosity of the extractant at low doses indicate yield of dimerization and recombination products.